Computer forensics and digital investigation with Encase Forensic v7 - Widup, Suzanne (McGraw-Hill Education, 2014)
"This practical, professional book provides a scenario-based guide to the industry's #1 digital forensics tool, EnCase Forensic Computer Forensics and Digital Investigation with EnCase Forensic shows how to uncover digital evidence in a fast, cost-effective, organized, and repeatable manner using the industry's leading digital investigation software. Part I addresses forensic readiness, setting up the software, and the basic interface. Part II lays out the case study used and how to navigate it step-by-step using the software. Part III details how to find clues and go deeper into investigations (finding hidden and deleted data). Part IV walks you through how to analyze the data, refine, and manipulate the results. Part V discusses the options for automating frequent tasks using EnCase Portable and the EnScript programming language. Sharpens the competitive edge of forensics practitioners through practice with the industry's #1 tool, EnCase Forensic Provides invaluable professional advice on the best working methods of digital forensic specialists An affordable learning option for this widely used tool Walks you through all the latest features to this first major software update in six years--EnCase Forensic v7 performs mobile device forensics (iPad, iPhone, Android, Blackberry, etc.), includes a completely revamped user interface, and streamlined organization of file, data, and report functions Commonly accessible evidence file toolkit allows you to put the book's case examples to the test "--